Educator perspectives on embedding Acknowledgement to Country practices in early learning centres in Australia. Issue 2 (June 2023) - Townley, Cris; Grace, Rebekah; Woodrow, Christine; Baker, Elise; Staples, Kerry; Locke, Michelle Lea; Kaplun, Catherine
This article explores the practices of 'Acknowledgement to Country' in Australian early childhood education contexts. Acknowledgement is a process of seeking out and honouring local Aboriginal Country and knowledge and investing in local resources of language, art, stories, nature and songs. Twenty educators across six early learning centres participated in semi-structured interviews to explore the experience, processes and resources that supported the implementation of Acknowledgement practices. Acknowledgement practices were not limited to a daily protocol but embedded in each centre's physical place and programming. Wanting to be respectful yet fearing offending Aboriginal people, most educators expressed feelings of uncertainty and under-confidence about what to do. Developing relationships with local Aboriginal people and identifying resources were also concerns. Acting from the heart with good intentions was regarded as a way forward together, with commitment, resources and a strong distributed pedagogical leadership culture, where educators felt supported to take small yet foundational steps.